Immunotherapy Makes Inroads in Head and Neck Cancer Treatment - Gohel, Shruti; Akhade, Amol (Indian Journal of Medical and Paediatric Oncology, 2025)
Immunotherapy has transformed the treatment landscape of metastatic head and neck squamous cell carcinoma (HNSCC), but its role in curative-intent settings remained elusive—until now. Recent data from two pivotal phase III trials, NIVOPOSTOP and KEYNOTE-689, mark a turning point by demonstrating statistically significant improvements in disease-free and event-free survival, respectively. However, the magnitude of benefit remains limited, subgroup efficacy is unclear, and overall survival data are immature. Given the logistical complexity and potential for overtreatment, these results warrant cautious interpretation. Future strategies must prioritize biomarker-driven selection, real-world feasibility, and long-term survival outcomes before immunotherapy can claim a definitive role in curative HNSCC.
Keywords: head and neck cancer; HNSCC; immunotherapy; neoadjuvant therapy